Gambaran Tingkat Kepuasan Perawat Dalam Menangani Pasien Covid-19 Di Ruang Isolasi RSUD Dr. Hasri Ainun Habibie - Alan Yusuf; Sabirin B. Syukur; Pipin Yunus (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Covid-19 is a virus that can cause disease, both in humans and in animals, in humans it can cause respiratory tract infections such as Middle East Respiratory Syndroma (MERS) and Severe Acute Respiratory Syndroma (SARS). Research purposes to find out description of the level of satisfaction of nurses in treating covid-19 patients. Type of qualitative research with descriptive research design. The total population is 31 nurses who area in isolation rooms A and B with total sampling. The results showed that the highest nurse satisfaction was very satisfied as many as 18 people and there were 12 nurses with a satisfied level of satisfaction and the lowest was dissatisfied with 1 person. So it was concluded that most nurses were very satisfied in handling covid-19 . Suggestions are that nurses are expected to continue to provide mutual support and motivation in providing services to patients, in order to get satisfaction in serving and patients also feel satisfied with the services provided.